Pengaruh Pajak Penghasilan Badan, Ukuran Perusahaan, Tax Haven Country, dan Kualitas Audit terhadap Agresivitas Transfer - Jessica Gracia; Amelia Sandra (Wahana Riset Akuntansi, 2022)
This study aims to examine the factors that can influence transfer pricing aggressiveness such as corporate income tax, firm size, tax haven country, and audit quality. The object in this study are 108 manufacturing companies listed on the Indonesia Stock Exchange throughout 2016-2018. The technique used in data analysing were descriptive analysis, pooling test, classic assumption test, and multiple linear regression analysis. The F-test result indicates that corporate income tax, firm size, tax haven country, and audit quality simultaneously affect to transfer pricing aggressiveness. From the result of the t-test of this study concluded that corporate income tax has no effect on transfer pricing aggressiveness in a positive direction. Firm size has no effect on transfer pricing aggressiveness in a negative direction.  Meanwhile, tax haven country variable has negative effect on transfer pricing aggressiveness. While, audit quality has positive effect on transfer pricing aggressiveness.Keywords: Transfer Pricing, Corporate Income Tax, Firm Size, Tax Haven Country, Audit Quality.